Methodology for determining the growth of urban sprawl in the capital cities of the Central American region (1975-1995-2014) - Vargas-Bolaños, Christian; Orozco-Montoya, Ricardo; Vargas-Hernández, Annie; Aguilar-Arias, Jairo (Revista Geográfica de América Central., 2019)
This paper presents the implementation of a methodology for determining the growth of urban sprawl in the capital cities of the Central American Region (CAR) during the period 1975-1995-2014. The objective of the investigation is to recreate the urban sprawl of the Central American capital cities throughout the studied years by means a methodology involving remote sensing and the implementation of various techniques for the processing and post-processing of Landsat satellite images. Additionally, photointerpretation, classification and GIS (Geographic Information Systems) digitalization techniques were used in determining the urban sprawls of each country for the period under consideration to provide a baseline for the comparative analysis of each capital city taking into account geopolitical elements and some related studies. (Se recomienda hacer pausa con punto para describir finalmente la utilidad del estudio). This study serves as input for future research on the analysis of urban planning as well as territorial planning.